Analisis Penentuan Margin Pembiayaan Murabahah pada PT. Bank Syariah X Cabang Pontianak - Hamsyi, Nur Fitriana (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2017)
The purpose of this research is to find out how to determine the margin of murabahah financing, and components considered by Bank Syariah X Pontianak Branch. This is a qualitative descriptive research by investigating directly to the field in order to get more detail informations.Data collections were done by conducting observation, interview, documentation and literature study. From the research results, it can be concluded that the determination of murabahah margin in Bank Syariah X Branch Pontianak was using base lending rate approach where the components were among others the cost of fund, overhead cost, expected return, and risk premium. The margin set by the Syariah Bank at the beginning of the contract and should not be changed until the end of the contract and this distinguishes Islamic banks with conventional banks.